Peningkatan Pemahaman Tentang Kemasan Pada UMKM Pengolah Rumput Laut - Rizianiza, Illa; Mungil, Diniar; Idhil, Andi (Universitas Nusantara PGRI Kediri, 2021)
The number of MSMEs in North Penajam Paser Regency is very large, especially MSMEs processing seaweed. Seaweed is one of the main commodities of North Penajam Paser Regency. However, the sales turnover of MSME products is still below the target. One of the factors that causes sales turnover has not reached the target is that the packaging of processed seaweed products is still very minimalist so that the attractiveness of buyers is not maximized. This Community Service Program aims to provide training and understanding to MSME members about the importance of packaging seaweed products. The training materials include attractive packaging types, how to make designs and the selection of appropriate packaging for processed seaweed products. The method of implementing this activity is training by giving lectures, discussions and practices that are carried out in an interesting and easy to understand manner for the trainees. The target of this Community Service activity is seaweed processing MSMEs who are members of the Self-Working Joint Marketing Processing Group (Poklahsar). The success of Community Service activities was measured by filling out questionnaires by training participants which were distributed before and after the training. Based on the results of filling out the questionnaire, it was concluded that for each packaging material presented, the level of understanding of the training participants increased to the maximum. However, the level of understanding of packaging design still cannot increase significantly. With this activity, it is hoped that MSME members understand knowledge about packaging well so that they can increase sales turnover of seaweed products.